2021
DOI: 10.17645/pag.v9i4.4525
|View full text |Cite
|
Sign up to set email alerts
|

Is the (Mass) Party Really Over? The Case of the Dutch Forum for Democracy

Abstract: Over the past decades, the Netherlands has witnessed the rise of several influential populist radical right parties, including the Pim Fortuyn List (Lijst Pim Fortuyn), Geert Wilders’s Party for Freedom (Partij voor de Vrijheid) and, more recently, the Forum for Democracy (Forum voor Democratie [FvD]). By analyzing the party’s organizational structures, this article seeks to determine whether the FvD may be considered a new “mass party” and to what extent ordinary members can exert influence over the party’s i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Empirical research has repeatedly confirmed that policy considerations are a prime explanatory factor for vote choices (Dalton 1985 ; Iversen 1994 ), including the choices of those who support a radical right-wing party (Van der Brug et al 2000 ; Rooduijn 2018 ). A policy voting model assumes that electoral competition works like a market with demand- and supply-side factors (e.g., Van Der Brug et al 2005 ; Van Hauwaert 2021 ; De Jonge 2021 ). Parties are expected to be successful if many voters share their policy positions on issues that voters care about, while there are few other parties that hold similar policy positions.…”
Section: Voting For Radical Right Partiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Empirical research has repeatedly confirmed that policy considerations are a prime explanatory factor for vote choices (Dalton 1985 ; Iversen 1994 ), including the choices of those who support a radical right-wing party (Van der Brug et al 2000 ; Rooduijn 2018 ). A policy voting model assumes that electoral competition works like a market with demand- and supply-side factors (e.g., Van Der Brug et al 2005 ; Van Hauwaert 2021 ; De Jonge 2021 ). Parties are expected to be successful if many voters share their policy positions on issues that voters care about, while there are few other parties that hold similar policy positions.…”
Section: Voting For Radical Right Partiesmentioning
confidence: 99%
“…He confirms that support for both parties is mainly driven by socio-cultural issue stances, while the (usually rather small) differences in sympathy for these two parties are linked to voters’ positions on socio-economic issues, where FvD attracts more socioeconomically liberal voters. FvD had initially presented itself as a ‘more reasonable’ alternative to the PVV (De Jonge 2021 , p. 288). Both of the party’s MPs were highly educated and affluent speakers (Baudet has a PhD in philosophy and the number two, Hiddema is a criminal defense lawyer).…”
Section: Voting For Radical Right Partiesmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the leader of the party, T. Baudet, appeals to the German civilization, the boreal [northern] world (boreale wereld), that is, to a certain historical and cultural community to which all the Dutch belong by birthright. The same characteristics distinguish the French National Rally (Rassemblement national): its leader, Marine Le Pen, calls for "freeing the French people from an arrogant elite," implying the homogeneity of both of these groups, and insists on the priority of the French over immigrants who do not share the French cultural heritage and the "general will" (De Jonge, 2021).…”
Section: Ethnicity and Politics: Points Of Intersectionmentioning
confidence: 99%